Studi Proses Produksi Tinta Gravure Violet dengan Parameter Capaian Warna - Ghaitsa Zahira Adni Shaffa; Emmidia Djonaedi; Rachmah Nanda Kartika (Pusat riset dan Inovasi Nasional, 2025)
The production process is a crucial aspect in ink formulation, especially violet spot color inks for gravure printing applications, which cannot be accurately reproduced through conventional process printing systems (CMYK). This research aims to optimize the production parameters of violet gravure inks that often exhibit color instability due to delays in the grinding and adjusting stages. The main focus of this research is to analyze the effect of variations in grinding duration, post-grinding aging time, and the amount of raw material on ink color yield, which is evaluated based on density, CIE Lab*, and ΔE parameters. The methodology used was a descriptive experiment on a laboratory scale. The results showed that the optimal treatment combination of grinding for 90 minutes, aging for 48 hours, and the use of 400 grams of material (P3K2L4) produced the highest density value (1.858) and ΔE (0.572), indicating color stability despite quantity variations. This finding indicates that optimization of grinding and aging time contributes to the improvement of pigment dispersion homogeneity and thermal stability of the resin, even without direct measurement of the transition glass temperature (Tg) value.